PENGARUH METODE MODELLING TERHADAP KEMAMPUAN BAHASA RESEPTIF PADA ANAK GANGGUAN PENDENGARAN UMUR TUJUH SAMPAI SEPULUH TAHUN DI SLB B YAYASAN REHABILITASI ANAK TUNA RUNGU WICARA - Rahmawati , Santika Yulia; Syah Fitri , Anisyah Dewi (Medical Journal of Nusantara, 2023)
Not all hearing impaired children can understand speech just by reading lips. That way, it requires the right way to improve receptive language skills, one of which is using the modeling method. By using the modeling method, it is hoped that children will more easily understand what other people are saying.The aim of this study was to determine the effect of the modeling method on receptive language skills in children with hearing loss aged seven to ten years. The type of research used is quantitative with a one-group pre and post test only design. The data collection technique uses total sampling with a sample of 8 respondents. The research instrument used was ROWPVT (Receptive One-Word Picture Vocabulary Test) and the modeling method module. The results of the pair t-test test obtained a significance of 0.000 which stated that there was an influence of the modeling method in improving receptive language skills in children with hearing loss. The correlation coefficient (r) obtained a result of 0.996 indicating a very strong influence between the modeling method and receptive language. Based on data analysis, the modeling method has an effect on improving receptive language skills in children with hearing loss.